Assessment of Anterior Segment Measurements with Swept Source Optical Coherence Tomography before and after Ab Interno Trabeculotomy (Trabectome) Surgery. (3rd October 2016) - Akil, Handan; Huang, Ping; Chopra, Vikas; Francis, Brian
Abstract : Purpose . To compare the changes of anterior segment parameters, assessed by swept source anterior segment optical coherence tomography (AS-OCT) after combined Trabectome-cataract surgery and Trabectome-only surgery in open angle glaucoma patients. Methods . Thirty-eight eyes of 24 patients with open angle glaucoma were scanned with swept source AS-OCT before and 4 weeks after combined Trabectome-cataract or Trabectome-only surgery. Intraocular pressure, number of medications, and AS-OCT parameters, such as angle opening distance at 500 and 750  μ m from the scleral spur (AOD500 and AOD750), trabecular-iris space area at 500 and 750 mm 2 (TISA500, TISA750), angle recess area at 500 and 750 mm 2 (ARA500, ARA750), trabecular iris angle (TIA), anterior chamber depth (ACD), anterior chamber width (ACW), and anterior chamber volume (ACV), were obtained before the surgery. These parameters were compared to evaluate whether the outcome of the surgery differed among the patients after the surgery. The width of the trabecular cleft was also measured for both groups. Results . The reduction of IOP and number of medications was found to be statistically significant in both groups (p < 0.001 ). ACD, ACV, and angle parameters such as AOD 500/750, TISA 500/750, ARA 500/750, and TIA500 showed significantly greater changes from the preoperative values to postoperative 1st month values in combined Trabectome-cataract surgery group (p < 0.05 ), whereas Trabectome-only group did not show statistically significant difference (p > 0.05 ). There was no statistically significant difference between two groups for the width of the trabecular cleft (p = 0.7 ). Conclusion . Anterior chamber angle parameters measured with swept source AS-OCT may be useful for evaluating glaucoma patients before and after Trabectome surgery with or without cataract surgery.